Diagnostic techniques for classical swine fever virus - Popescu, Luca Nicolae (Kansas State University, 2017)
Classical swine fever virus (CSFV) is an enveloped, positive strand RNA virus, and member of the genus Pestivirus. It is a highly infectious and transmissible swine pathogen that threatens the global swine industry. The United States has been free of CSFV since 1977, however, monitoring the millions of domestic and feral pigs present in the US puts a significant strain on national surveillance efforts. There are no validated diagnostic techniques that can simultaneously sample multiple pigs (i.e. all pigs in a pen or barn). Similarly, there are no validated serological assays that can quickly test for CSFV without cross-reacting with other pestiviruses. The purpose of the first study was to establish a moderate CSFV-infectious model and determine how a single oral fluid sample from a pen of pigs can function as a diagnostic sample for detecting CSFV. Oral fluid (OF) and serum samples were collected from 10 pigs experimentally infected with CSFV Paderborn strain. Using RT-PCR, CSFV was detected in OF on 8 days post infection (dpi), and in the serum of one pig on 6 dpi. A single OF sample can, therefore, take the place of 10 serum samples to detect CSFV in a population. In a second study, monoclonal antibodies reactive to CSFV glycoproteins were generated in mice immunized with recombinant E2 and Erns antigens. Five E2-specific clones and two Erns-specific clones showed reactivity to CSFV-infected. Epitope mapping of the E2 clones showed that all reacted with the N-terminal portion of E2; a region highly variable among pestiviruses. Together with OF sampling, monoclonal antibodies can be used to develop new tools for improving CSF surveillance in large swine populations.
Keywords: Foreign animal disease; Diagnostics; Oral fluids; Monoclonal antibodiesClassical swine fever virus